The study of prussian blue as cathode material for sodium-ion batteries / Chen Yuncai - Chen , Yuncai (2019)
The introduction of electric vehicles (EVs) into the automotive market has boosted the advancement of energy storage technology. Although lithium-ion batteries (LIBs) could provide a solution to the emerging EV market, it needs to overcome the issue of high material cost and limited resources. This leads the research direction to sodium-ion batteries (SIBs), the most potential alternative batteries with infinite sodium resource from the ocean and earth crust. In current work, Prussian Blue (PB) was synthesized by the facile one step solution-precipitation method at room-temperature. Ascorbic acid and poly (vinylpyrrolidone) (PVP) were used as the chelating agents. The as-prepared PB was characterized by element analysis, energy dispersive X-ray spectroscopy (EDX), thermogravimetric analysis (TGA), X-ray diffraction (XRD), high resolution transmission electron microscope (HRTEM), field emission scanning electron microscopy (FESEM) and X-ray photoelectron spectroscopy (XPS). The formula of the as-prepared PB has been obtained as Na0.58Fe[Fe(CN)6]0.93□0.07·1.67H2O with a 3-5 % water content. Two pairs of redox peaks are shown in cyclic voltammetry (CV) curve. The peaks at 3.15 V / 2.74 V correspond to high-spin Fe3+/Fe2+ bonding to N atoms of C≡N and those at 3.78V / 3.63V correspond to low-spin Fe3+/Fe2+ bonding to C atoms of C≡N. The battery exhibited a discharge specific capacity (DSC) of 133 mAh g-1 with an efficiency of almost 100 % at 0.1 C. At 2 C, a DSC of 102 mAh g-1 was obtained and the SIBs exhibited a good cyclability with more than 89 % retention after 200 galvanostatic charge/discharge (GCD) cycles.